Treatment‐induced cerebral sinus venous thrombosis in childhood acute lymphoblastic malignancies: New risk factors to consider. Issue 11 (29th July 2021) - El‐Khoury, Habib; Saifi, Omran; Haddad, Salame; Chahrour, Mohamad; Ghanem, Khaled M.; Mubarak, Yaacoub; Tamim, Hani; Makki, Maha; Zakka, Cyril; Chan, Anthony K.; Mahfouz, Rami; Tarek, Nidale; et al.
Abstract: Background: Cerebral sinus venous thrombosis (CSVT) is one of the many side effects encountered during acute lymphoblastic leukemia (ALL) therapy. Due to the rarity of cases, lack of data, and consensus management, no recommendations exist to target the population at risk. Methods: This is a retrospective chart review of 229 consecutive patients diagnosed with ALL with an age range of 1–21 years, treated at the Children's Cancer Center of Lebanon between October 2007 and February 2018. Results: The incidence of CSVT was 10.5%. Using univariate analysis, increased risk of CSVT was observed with male gender, age >10 years, T‐cell immunophenotype, intermediate/high‐risk disease, maximum triglyceride (TG) level of >615 mg/dl, presence of mediastinal mass, and larger body surface area (BSA). With multivariate analysis, the only statistically significant risk factors were maximum TG level, BSA, presence of mediastinal mass, and risk stratification (intermediate/high risk). Conclusion: Our study was able to unveil TG level of >615 mg/dl, mediastinal mass, and a larger BSA as novel risk factors that have not been previously discussed in the literature.